THE REVITALIZATION OF ISLAMIC ART IN THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION BASED ON CULTURAL VALUES - Wiwi Yuniarti; Adawiyah Pettalongi; Ubadah Ubadah; Andi Anirah (LP2M IAI Al-Khairat Pamekasan, 2026)
The revitalization of Islamic art in the development of culturally value-based Islamic Religious Education (ISRE) has become a strategic issue in a global context marked by cultural homogenization and an identity crisis, as well as in a national context facing the challenges of value degradation and minimal integration of local culture into learning. The urgency of this study lies in the need to present an approach to Islamic Religious Education that is contextual, humanistic, and adaptive to cultural diversity. This research aims to analyze the role of Islamic art as a medium for revitalizing cultural values ​​in the development of ISRE and its contribution to the formation of student character. The methodology employed a qualitative approach with literature studies, sourced from books, scientific articles, and relevant documents, and data collection through documentation. Data analysis was conducted descriptively and analytically through reduction, categorization, and interpretation. Data validity was maintained through source triangulation and diligent observation. The results indicate that Islamic art has integrative potential in internalizing aesthetic, spiritual, and social values ​​that strengthen cultural identity. These implications provide theoretical contributions to the development of the concept of culture based ISRE, as well as practical contributions to contextual learning innovations relevant to the dynamics of contemporary education and the needs of Indonesia's current multicultural society.